Proceso de ASC - PERSONALIZACION POLITICA: UN ANALISIS COMPARADO DE LA COMPETENCIA ELECTORAL DE LOS PARTIDOS POLITICOS EN COLOMBIA (2021)
The personalization of politics is an increasingly common phenomenon in contemporary dynamics. Theoretical and empirical approaches, both theoretical and empirical, mostly start from axiological positions on the phenomenon, imprinting negative connotations to its expression. The exceptions are the authors who approach the phenomenon with explanatory interest and to understand more about the factors that promote it or the expressions it has. This research postulates the importance of continuing to refine the proposal of quantitatively analyzing the phenomenon, an idea initiated in the previous project by the Semillero, with the purpose of offering an alternative of interpretation totally detached from evaluative positions on this phenomenon. Thus, this proposal justifies the reasons for the continuity of the analysis of the phenomenon for the Colombian case, involving other types of elections at the subnational level. The main aspects of the methodological proposal that will involve the application of the comparative method and the theoretical aspects that support the relevance of this proposal are pointed out.